2018
DOI: 10.1038/s41598-018-31181-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and induction of prophages in human gut-associated Bifidobacterium hosts

Abstract: In the current report, we describe the identification of three genetically distinct groups of prophages integrated into three different chromosomal sites of human gut-associated Bifidobacterium breve and Bifidobacterium longum strains. These bifidobacterial prophages are distantly related to temperate actinobacteriophages of several hosts. Some prophages, integrated within the dnaJ2 gene, are competent for induction, excision, replication, assembly and lysis, suggesting that they are fully functional and can g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 69 publications
(109 reference statements)
1
19
0
Order By: Relevance
“…Future studies are warranted to better understand the interaction between B. pseudocatenulatum prophage and its host by exploring the existence of some genetic elements in prophage driving bacterial evolution, or functional gene clusters helping host adaptation to harsh environment, as shown in the previous study on marine bacteria (Castillo et al, 2018). Besides, the isolation of difficult-to-culture phages from culturable bacteria by prophage induction could be used to improve our understanding of the bacteria-phage network (Mavrich et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies are warranted to better understand the interaction between B. pseudocatenulatum prophage and its host by exploring the existence of some genetic elements in prophage driving bacterial evolution, or functional gene clusters helping host adaptation to harsh environment, as shown in the previous study on marine bacteria (Castillo et al, 2018). Besides, the isolation of difficult-to-culture phages from culturable bacteria by prophage induction could be used to improve our understanding of the bacteria-phage network (Mavrich et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative genomic analyses in early studies have shown that more than 50% of bacteria possess prophages (Canchaya et al, 2003) whilst recent study showed that the prevalence of prophages within murine gut microbiota is much higher (Kim and Bae, 2018). However, prophages can be activated under certain conditions, such as UV light (Guo et al, 2016) or chemicals (Goerke et al, 2006;Mavrich et al, 2018). A recent study also showed that fructose and short-chain fatty acids could promote prophage induction in Lactobacillus reuteri (Oh et al, 2019a), suggesting the effect of sugar metabolism on phage production in human gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Faecalibacterium and Bifidobacterium are among the most predominant bacteria in healthy human microbiota in adulthood and infancy, respectively (Yatsunenko et al, 2012), but efforts to isolate bacteriophages infecting these predominant bacterial genera have proven unsuccessful, despite the presence of numerous prophages in their genomes. Recently, induction of prophages and secretion of Siphoviridae and Myoviridaetype viral particles from Faecalibacterium and Bifidobacterium have been reported (Cornuault et al, 2018;Mavrich et al, 2018).…”
Section: Diversity and Individuality Of Human Gut Phageomesmentioning
confidence: 99%
“…al. recognized and classified all prophage-like elements (referred to as bifidoprophages) present in 48 genomes of type strains belonging to different bifidobacterial species [24] and Mavrich et al characterized three of these identified groups of prophages integrated in members of B. breve and B. longum species by means of induction experiments [70]. In the current study, the screening for bifidoprophages was further extended to 625 different bifidobacterial genomes, resulting in the identification of 598 putative and apparently complete prophage sequences (Table S1).…”
Section: The Predicted Mobilome Of the Bifidobacterium Genusmentioning
confidence: 99%